The effect of the combustion channels on the compressive strength of porous NiTi shape memory alloy fabricated by SHS as implant material - Kaya, Mehmet; Orhan, Nuri; Tosun, Guel (Pergamon-Elsevier Science Ltd, 2010)
Porous NiTi shape memory alloy (SMA) with ideal porosity and high compressive strength as an implant material was fabricated by self-propagating high-temperature synthesis (SHS). In this study, a new ignition technique high voltage electric arc was used to ignite the green specimens and control the orientation of combustion channels which effect compressive strength. It was determined that the compressive strength of specimens was increased when the combustion channels were parallel along the specimen axis, and the compressive strength was decreased when the combustion channels were perpendicular to specimen axis. The desired phases such as B2(NiTi) and B19' (NiTi) were dominant while the second phases (Ni4Ti3 and NiTi2) in small amount. The undesired phases (such as pure Ni and Ni3Ti) for biocompatibility are not found in the structure. The transformation temperatures were higher for medical applications by heat treatment and partly decreased at every next thermal cycle where the heating rate of the specimen was increased. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Porous NiTi shape memory alloy; SHS; Implant material; Compressive strength